2013
DOI: 10.1371/journal.pone.0056877
|View full text |Cite
|
Sign up to set email alerts
|

Drug Absorption Efficiency in Caenorhbditis elegans Delivered by Different Methods

Abstract: Background Caenorhbditis elegans has being vigorously used as a model organism in many research fields and often accompanied by administrating with various drugs. The methods of delivering drugs to worms are varied from one study to another, which make difficult in comparing results between studies.Methodology/Principal FindingsWe evaluated the drug absorption efficiency in C. elegans using five frequently used methods with resveratrol with low aqueous solubility and water-soluble 5-Fluoro-2′-deoxyuridine (FUD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 50 publications
(40 reference statements)
2
60
0
Order By: Relevance
“…This result is encouraging in light of a recent study reporting that drug uptake by C. elegans is comparable to that of mice, especially when they are treated in a LC environment. 78 Moreover, our recent study with SAS-0132 has demonstrated an improvement in cognitive performance in transgenic AD mice. 8 Finally, the dose-dependent variations observed even within this small compound collection show that our microfluidic screening technology is an excellent platform for assessing structure–activity-relationships.…”
Section: ■ Discussionmentioning
confidence: 98%
“…This result is encouraging in light of a recent study reporting that drug uptake by C. elegans is comparable to that of mice, especially when they are treated in a LC environment. 78 Moreover, our recent study with SAS-0132 has demonstrated an improvement in cognitive performance in transgenic AD mice. 8 Finally, the dose-dependent variations observed even within this small compound collection show that our microfluidic screening technology is an excellent platform for assessing structure–activity-relationships.…”
Section: ■ Discussionmentioning
confidence: 98%
“…This applies even more in the light of an encapsulated pharynx, isolated from the rest of the worm by a specialized basal lamina. Moreover, recent investigations revealed that the more economic approach of spotting compounds on the agar surface achieved lower absorption effi ciency in worms when compared with other drug delivering methods, as pouring compounds together with agar ( 38 ). In the case of the spot method, the solution will immerse into the NGM agar, which reduces the availability.…”
Section: Effects Of Cyp Eicosanoids and Neurohormones On Food Uptakementioning
confidence: 99%
“…For these reasons, higher initial compound concentrations (25–100 µM) are typically used in C. elegans -based drug screens. A recent study, however, suggests that drug uptake by C. elegans is comparable to that of mice [51]. The study also found that culture and assay methods - liquid vs agar-based cultures, E. coli preparation and when and how the drugs were added – had significant effects on drug efficacy.…”
Section: Caveats and Challenges With C Elegans-based Drug Discoverymentioning
confidence: 95%
“…The study also found that culture and assay methods - liquid vs agar-based cultures, E. coli preparation and when and how the drugs were added – had significant effects on drug efficacy. The use of heat-killed, rather than live E. coli increased the uptake of drugs as measured by higher internal drug concentrations [51]. The killing of E. coli presumably prevented drug metabolism by the bacteria which in turn increased drug availability [51].…”
Section: Caveats and Challenges With C Elegans-based Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation